Medication Adherence in Type 2 Diabetes Melitus Patients - Nawang Wulan Nago Pitasari; Farhan Imba; Innal Saitis; Ferdinta Setyawan (Indonesian Journal of Global Health Research, 2026)
Type 2 Diabetes Mellitus is a chronic disease characterized by metabolic disorders, marked by elevated blood glucose levels exceeding the normal range. This study aimed to determine the level of adherence of type 2 diabetes mellitus patients to antidiabetic medication at Harapan Community Health Center (Puskesmas Harapan), Jayapura Regency. The research employed a descriptive design using the Morisky Medication Adherence Scale (MMAS-8) questionnaire as the data collection instrument, involving 50 outpatient type 2 diabetes mellitus patients at Puskesmas Harapan. Sampling was conducted using purposive sampling. Data were analyzed using frequency distribution. The results showed that the majority of respondents fell into the moderate adherence category, with 24 respondents (48%), high adherence in 16 respondents (32%), and low adherence in 10 respondents (20%). Medication adherence among type 2 diabetes mellitus patients at Harapan Community Health Center, Jayapura Regency, was generally moderate, with most patients being elderly females.